Association of glutathione S-transferase T1 and M1 genotypes with chronic liver diseases among Filipinos. - Baclig, M; Alvarez, MR; Lozada, X; Mapua, C; Lozano-Kühne, J; Dimamay, M; Natividad, F; Gopez-Cervantes, J; Matias, R (2012)
The glutathione S-transferase (GST) supergene family is made up of four gene families responsible for the biotransformation of drugs and other xenobiotics. Genetic variations in this supergene family influence individual detoxification levels and may contribute to the development of cancer. A hospital-based case-control study was conducted to evaluate the association between GST polymorphism among Filipino patients positive for hepatitis B virus (HBV DNA) and clinically diagnosed as either with chronic active hepatitis, liver cirrhosis, and hepatocellular carcinoma as well as normal individuals negative for HBV infection. Multiplex PCR was used to detect the presence or absence of the GSTT1 and GSTM1 polymorphisms in peripheral blood. DNA sequencing of the S gene region of the virus was used to determine the predominant genotype found among HBV-infected patients. Our results showed that the odds of having a chronic liver disease is only 0.95 (95% CI 0.58-1.57) among those with GSTT1 null genotype compared to those with GSTT1+ genotype. On the other hand, the odds of chronic liver disease is 17.85 times (95% CI 7.34-43.45) for those with GSTM1 null genotype compared to those with GSTM1+ genotype. Using the GSTT1+/GSTM1+ genotype as the reference, both GSTT1+/GSTM1- (OR 16.61; 95% CI 6.69-41.22) and GSTT1-/GSTM1- (OR 11.91; 95% CI 4.48-31.66) genotypes seem to be risk factors for chronic liver disease. From our observations, we conclude that polymorphism in GSTM1 null genotype (OR 17.85; 95% CI 7.34-43.45) seem to be associated with an increased risk of chronic liver disease among Filipinos.